Hubungan Hukum Terhadap Kepemilikan Hak Cipta Yang Dijadikan Merek Bagi Pencipta Dan Pemegang Merek - Pratama, Revie Rachmansyah; Roisah, Kholis (Universitas Semarang, 2025)
This research aims to analyze the characteristics, legal protection, application of principles between copyright and trademarks, and the potential disputes that arise. The urgency of this research lies in the need for harmonization between the declarative principle in copyright and the first-to-file principle in trademarks to address the potential legal conflicts that often arise due to the overlapping protection of these two intellectual property rights. This research method uses a normative juridical type of research with secondary data as the main data. The research results indicate that differences in protection principles can trigger legal disputes, especially when elements of copyrighted works are used as trademarks without permission. The novelty of this research is the recommendation for the implementation of cross-database mechanisms and policies for the cancellation of trademark registrations that violate copyright to prevent conflicts. The novelty of this research is to examine the legal relationship between copyright and trademark more holistically, providing an approach based on the Economic Analysis of Law (EAL) to assess the effectiveness of legal protection. The recommendation of this research is that cross-database mechanisms and policies for the cancellation of trademark registrations that violate copyright should be implemented to prevent disputes. In conclusion, the harmonization of the declarative principle and the first-to-file principle can be achieved through enhanced synergy among relevant institutions, education for creators and entrepreneurs, and strengthened regulations to ensure fairness, legal certainty, and balanced protection of economic rights. Penelitian ini bertujuan untuk menganalisis menganalisis karakterisitik, perlindungan hukum, penerapan prinsip antara hak cipta dan merek serta potensi sengketa yang terjadi. Urgensi penelitian terletak pada perlunya harmonisasi antara prinsip deklaratif dalam hak cipta dan asas first to file dalam hak merek untuk mengatasi potensi konflik hukum yang sering terjadi akibat tumpang tindih perlindungan kedua hak kekayaan intelektual ini. Metode penelitian ini menggunakan jenis penelitian yuridis normatf dengan menggunakan data sekunder sebagai data utama. Hasil penelitian menunjukkan bahwa perbedaan prinsip perlindungan dapat memicu sengketa hukum, terutama ketika elemen karya cipta digunakan sebagai merek tanpa izin. Kebaruan penelitian ini adalah mengkaji hubungan hukum antara hak cipta dan hak merek secara lebih holistik, memberikan pendekatan berbasis Economic Analysis of Law (EAL) untuk menilai efektivitas perlindungan hukum. Rekomendasi penelitian ini bahwa implementasi mekanisme lintas basis data dan kebijakan pembatalan pendaftaran merek yang melanggar hak cipta untuk mencegah sengketa. Kesimpulannya, harmonisasi prinsip deklaratif dan asas first to file dapat dicapai melalui peningkatan sinergi antara lembaga terkait, edukasi kepada para pencipta dan pelaku usaha, serta penguatan regulasi untuk memastikan keadilan, kepastian hukum, dan perlindungan hak ekonomi yang seimbang.